Developing a framework for adopting environmental manufacturing practices: learning from breweries. Issue 8 (11th June 2022) - Ball, Peter; MacBryde, Jill
Abstract: There is a growing desire to reduce the environmental impact of manufacturing operations through implementing new practices. There is a reasonable literature on environmental practices and the benefits they can bring. However, the literature is weak in two respects: firstly, it is heavily reliant on practices of leading firms; secondly, there is little focus on understanding the conditions that foster the adoption of such practices. This paper addresses these shortfalls by presenting evidence of how any firm can start to improve their resource efficiency using new practices. Studying organizations with similar market conditions and production systems allows us to look at a breadth of firms in a single supply chain tier, with a range of environmental maturity. A grounded approach employing interviews, workshops and observation uncovers the conditions that help and hinder adoption of new ways of working. Specifically, the motivations for cost reduction through resource efficiency, aided by communities of practice but hindered by organisational barriers. Combining this with learning from theory, this paper advances environmental practice in manufacturing through learning from the experiences of UK brewers. The work contributes to knowledge by framing how companies of all shapes and sizes within a sector (not just the leading companies) can advance by adopting practices and avoiding barriers.